HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL DAN PENGEMBANGAN KARIR DENGAN KEPUASAN KERJA - Mawadah, Ina (Universitas Ahmad Dahlan, 2012)
ABSTRACTThis study aimed to determine the relationship between interpersonal communication and career development with job satisfaction. Subjects were all employees of Malioboro Inn Hotel Yogyakarta. This study used quantitative methods. Data collection tool that was used is the Interpersonal Communication Scale, Scale of Career Development and Job Satisfaction Scale. The statistical analysis that was used is multiple regression analysis. The overall computational research data using SPSS 18.0 for windows. The analysis by using multiple regression found significant relationship between interpersonal communication and career development with job satisfaction (R = 0.618, p = 0.000). The results of the analysis of product moment between interpersonal communication with job satisfaction showed r = 0.513 with a significance level (p) = 0.001 (p <0.01) and between career development with job satisfaction showed r = 0.415 with a significance level of 0.007 (p <0.01 ). Contribution of interpersonal communication on job satisfaction was 23.76%, while the effective contribution of career development to job satisfaction was 14.44%, and the effective contribution of interpersonal communication and career development on job satisfaction was 38.2%. There was a significant relationship between interpersonal communication and career development with job satisfaction. The majority of research subjects have job satisfaction, communication, interpersonal and career development in the medium category.Keywords: job satisfaction, interpersonalcommunication, career development.